The Finite Element Analysis On Hexagonal Ring Under Simple Lateral Loading - Said, Md Radzai; Yuhazri, Yaakob; Lau, Saijod T.W. (Getview Limited, 2012)
Lateral crushing of hexagonal ring under quasi-static loading were analysed using ABAQUS/Standard Finite Element (FE) Method package. The modes of deformation and load displacement characteristics were predicted and the same were compared with experimental results. The material modelling of elastic-perfectly plastic and nominal stress-plastic strain were compared.The experimental results found that the quarter model using CPE6H with elastic-perfectly plastic material is good enough to obtain a satisfactory result.